EFL STUDENTS’ METACOGNITIVE LEARNING STRATEGIES IN ESSAY WRITING - Roslaini; Inka Dwiyanti (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2023)
This study focused on the metacognitive learning strategies of EFL students related to their activities in writing an essay. This study aimed to know to what extent EFL students used metacognitive learning strategies and how they used them in writing essays. The data were collected using questionnaires and interviews. Fifty students from English Education Department filled in the questionnaire and nine students were taken to participate in the interview. All of the participants had taken Essay Writing from the previous semester. After analysing the questionnaires, the findings indicated that in using metacognitive learning strategies most students used planning (4.08), monitoring (4.06), and evaluating (4.14) in writing their essays. Thus, it can be categorized into good criteria. From the interview, it revealed that most students used planning activities such as doing reading preparation after deciding the topic, generating ideas, and making an outline to organize their ideas. In monitoring, it was found that the students commonly monitored the development of their ideas during writing and checking their writing regarding to the content, organization, and language used during the process of their writing. For evaluating, the students used self-evaluation, peer review, and feedback from the lecturer to evaluate their essays. Finally, the study revealed that the students commonly implemented metacognitive learning strategies in their essay writing.